Cutting Tools

JP2024519616A5Active Publication Date: 2025-03-25SANDVIK COROMANT
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2023568243
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2021-05-07
Filing Date
2022-05-06
Publication Date
2025-03-25
Estimated Expiration
2042-05-06

AI Technical Summary

Technical Problem

CVD coated cutting tools with Ni-containing cemented carbide substrates face issues of intermetallic phase formation between the substrate and Ti-containing coatings, leading to reduced coating adhesion and wear resistance due to the high reactivity of Ni with Ti, especially during chemical vapor deposition.

Method used

A cutting tool with a Ni-containing cemented carbide substrate coated with a W(C x N 1-x) y layer as a diffusion barrier, followed by a TiN and TiCN layer, and topped with an α-Al 2 O 3 layer, where x is between 0.6 and 0.8, and y is between 1.1 and 1.8, preventing intermetallic phase formation and enhancing coating adhesion.

Benefits of technology

The W(C x N 1-x) y layer acts as a diffusion barrier, stabilizing the coating and improving wear resistance, resulting in enhanced tool life and performance in metal cutting applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

The present invention relates to a coated cutting tool comprising a substrate at least partially coated with a coating, said substrate being made of a hard metal composed of hard constituents in a metal bond, said metal bond comprising more than 60% by weight of Ni, said coating comprising two or more layers, the layer adjacent to the substrate being W(C x N 1-x ) y layer, where 0.6≦x≦0.8 and 1.1≦y≦1.8, and W(C x N 1-x ) y The layer thickness is 0.4 to 7 μm.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a coated cutting tool. The cutting tool is CVD coated, the substrate is a cemented carbide, and the metal binder in the cemented carbide comprises Ni. The CVD coating is a W(C x N 1-x ) y The inner layer is [Background technology]

[0002] CVD-coated cutting tools are well known in the field of cutting tools for chip-forming metal cutting operations. The substrate of the coated cutting tools is usually a cemented carbide, which is made of WC in a Co metal binder. Alternative binders without Co or with reduced amounts of Co have been developed, but are still rare or absent in market products. The production of the cemented carbide itself, as well as the coating of the cemented carbide, is demanding, due to interactions between the gas phase and the cemented carbide, especially during chemical vapor deposition, which is carried out using hot reactive gases.

[0003] Among alternative metallic binders, a mixture of Ni and Fe is a promising candidate. Ni exhibits high reactivity with, for example, Ti, and a large amount of Ni in a hardmetal causes problems in the chemical vapor deposition of Ti-containing coatings, since intermetallic phases such as Ni3Ti form at the interface between the hardmetal and the coating and also within the coating. Intermetallic phases such as Ni3Ti at the interface or lower parts of the Ti-containing coating reduce the coating adhesion and adversely affect the wear resistance of coatings subsequently deposited on the Ti-containing coating.

[0004] The problem of Ni3Ti formation during deposition of TiN coatings on Ni metal substrates has been analyzed in L. von Fieandt et al., "Chemical vapor deposition of TiN on tansition metal substrates", Surface and Coatings Technology 334 (2018) 373-383. It was concluded that the formation of Ni3Ti can be reduced by excess N2 partial pressure and low H2 partial pressure during the CVD process.

[0005] It is an object of the present invention to provide a cutting tool having a Ni-containing cemented carbide substrate with a wear-resistant CVD coating. It is also an object of the present invention to provide a method for depositing a coating comprising a layer of 001-oriented α-Al2O3 on a Ni-containing cemented carbide substrate, in particular a substrate containing a metal binder with more than 60 wt.% Ni. Summary of the Invention

[0006] At least one of the above mentioned objects is achieved by a cutting tool according to claim 1. Preferred embodiments are disclosed in the dependent claims.

[0007] The present invention relates to a coated cutting tool comprising a substrate at least partially coated with a coating, said substrate being made of a hard metal composed of hard constituents in a metal bond, said metal bond comprising more than 60% by weight of Ni, said coating comprising two or more layers, the layer adjacent to the substrate being W(C x N 1-x ) y layer, where 0.6≦x≦0.8 and 1.1≦y≦1.8, preferably 0.67≦x≦0.72 and 1.17≦y≦1.76, and W(C x N 1-x ) y The layer thickness is 0.4 to 7 μm.

[0008] Cemented carbide materials are useful in extremely demanding cutting tool applications due to their high hardness and high wear resistance combined with high toughness. Cemented carbide materials are produced by powder metallurgy methods, where starting powders are mixed, milled, formed into green bodies, presintered, and sintered.

[0009] Cemented carbide materials generally consist of hard constituents of WC in a metal binder, for example Co or Co combined with Ni and Fe, and optional carbides and / or nitrides, for example TiC. In the present invention, the metal binder comprises more than 60 wt.% Ni. A high content of Ni in the metal binder has been shown to be particularly demanding in CVD deposition. Cemented carbide compositions, and in particular metal binder compositions, can be analyzed by chemical analysis.

[0010] Surprisingly, W(C) having the above composition and a thickness of 0.4 μm or more x N 1-x ) y It has been found that the W(C) layer can prevent the Ni in the metal binder from adversely affecting the subsequently deposited layers. x N 1-x ) y The layer had the function of a diffusion barrier layer and prevented the substrate from affecting the coating quality. Thus, W(C x N 1-x ) y The layer may prevent the formation of reaction products between Ti and Ni.

[0011] W(C) of the present invention is 1.1≦y≦1.8, preferably 1.17≦y≦1.76. x N 1-x ) y The high amount of C and N in the layer is believed to contribute to a stable layer even when the coating is exposed to metal cutting applications where high pressures and temperatures are typically implied.

[0012] In one embodiment of the present invention, W(C x N 1-x ) yThe layer is in the hexagonal phase. This is advantageous because the thermal expansion coefficient of hexagonal W(C,N) is similar to that of WC. This may prevent the formation of thermal cracks during the manufacture of the coated cutting tool and may also have an impact on the life of the tool since cutting tools are typically exposed to thermal cycles during use in cutting, such as interrupted cutting. By hexagonal phase, we mean the δ-WC hexagonal phase.

[0013] In one embodiment of the present invention, W(C x N 1-x ) y The layers are composed of columnar grains, which herein means that the aspect ratio of grain length to grain width is greater than 1.

[0014] In one embodiment of the present invention, W(C x N 1-x ) y The average grain width of the layer is 0.14 to 0.40 μm, preferably 0.15 to 0.30 μm.

[0015] In one embodiment of the present invention, W(C x N 1-x ) y The layer is W(C x N 1-x ) y The orientation measured by EBSD for a cross section of the layer is shown. The analysis area is 100 μm in width and 100 μm in height. x N 1-x ) y is the layer thickness, and W(C x N 1-x ) y The surface normal of the layer is parallel to the growth direction of the layer, and more than 75% of the analyzed area is W(C x N 1-x ) y The layer has a <11-20> direction within 30 degrees of the surface normal, and preferably 80% or more of the analysis area is within 30 degrees of the <11-20> direction.

[0016] In one embodiment of the present invention, the metal binder comprises 65-90 wt % Ni, preferably 70-87 wt % Ni, more preferably 75-85 wt % Ni.

[0017] In one embodiment of the present invention, the metal binder comprises 10-20 wt % Fe, preferably 10-15 wt % Fe.

[0018] In one embodiment of the present invention, the metal binder comprises 3-8 wt. % Co, preferably 5-6 wt. % Co.

[0019] In one embodiment of the present invention, the metal binder comprises 65-90 wt % Ni, 10-20 wt % Fe and 3-8 wt % Co. In one embodiment, the metal binder is a Ni-Fe-Co alloy.

[0020] In one embodiment of the present invention, the content of the metal binder in the cemented carbide is 3-20% by weight, preferably 5-15% by weight, and most preferably 5-10% by weight.

[0021] In one embodiment of the present invention, the coating comprises a TiN layer, and the thickness of the TiN layer is 0.3-1 μm.

[0022] In one embodiment of the present invention, the coating comprises a TiCN layer, preferably the thickness of the TiCN layer is 6-12 μm.

[0023] In one embodiment of the present invention, the TiCN layer exhibits a texture coefficient TC(hkl) defined according to the Harris equation, measured by X-ray diffraction using Cu Kα radiation and θ-2θ scanning: TIFF2024519616000002.tif19170where I(hkl) is the measured intensity (integrated area) of the (hkl) reflection, I0(hkl) is the standard intensity according to ICDD PDF-Card No. 42-1489, n is the number of reflections, the reflections used in the calculation are (1 1 1), (2 0 0), (2 2 0), (3 1 1), (3 3 1), (4 2 0), (4 2 2) and (5 1 1), and TC(4 2 2) is ≥ 3.5.

[0024] In one embodiment of the present invention, the total thickness of the coating is between 2 and 25 μm.

[0025] In one embodiment of the present invention, the coating is preferably a coating on the outermost surface of the cutting tool and W(C x N 1-x ) y The substrate further includes a layer of Al2O3 located between the first and second layers.

[0026] In one embodiment of the present invention, the Al2O3 layer is an α-Al2O3 layer.

[0027] In one embodiment of the present invention, the α-Al2O3-layer exhibits a texture coefficient TC(hkl) defined according to the Harris formula, measured by X-ray diffraction using Cu Kα radiation and θ-2θ scanning, where I(hkl) is the measured intensity (integrated area) of the (hkl) reflections, I0(hkl) is the standard intensity according to ICDD PDF-Card No. 00-010-0173, n is the number of reflections used in the calculation, the (hkl) reflections used being (1 0 4), (1 1 0), (1 1 3), (0 2 4), (1 1 6), (2 1 4), (3 0 0) and (0 0 12), characterized in that TC(0 0 12) is ≧7, preferably ≧7.2.

[0028] In one embodiment of the present invention, the thickness of the Al2O3 layer is 4-8 μm.

[0029] In one embodiment of the present invention, the cutting tool is a drill, a milling insert or a turning insert, preferably a turning insert.

[0030] In one embodiment, W(C x N 1-x ) y The layer is a CVD layer. In one embodiment, the TiCN layer is a CVD layer. In one embodiment, the Al2O3 layer is a CVD layer. In one embodiment of the present invention, the coating is a CVD coating.

[0031] Further objects and features of the present invention will become apparent from the following definitions and examples considered in conjunction with the accompanying drawings.

[0032] method W(C x N 1-x ) y Layer Composition The 36 MeV beam was detected at an incidence angle of 67.5° relative to the surface normal and a recoil detection angle of 45°. 127 I 8+ Using the beam, W(C x N 1-x ) y The elemental composition of the layer was analyzed. A gas ionization chamber detector was used to measure the scattering 127 I 8+ It detects both the number and energy of the ions, but more importantly, it also detects the atoms that recoil from the sample. This analysis was combined with a time-of-flight analyzer, which allows calculation of atomic masses as well as energy detection, thereby providing an elemental depth profile of the coating.

[0033] Data analysis was performed using Potku software. The depth profile was integrated from approximately 30 to 200 nm from the sample surface to obtain a 250 × 10 15 ~2000×10 15 atoms / cm 2 The concentration was calculated.

[0034] W(Cx N 1-x ) y Layer facies analysis W(C x N 1-x ) y Grazing incidence X-ray diffraction (GI-XRD) measurements were performed to analyze the phase composition of the grains in the layers. An incidence angle of 1° was used. GI-XRD measurements were performed using a Philips MRD X'Pert diffractometer with a Cu Kα source and a Gobel mirror forming a parallel incidence beam. A mirror slit was used to allow a 1.4 mm beam, and a 0.04 rad Soller slit was placed on the side of the primary beam. The secondary beam was collimated with a 0.27° collimator, and the intensity was recorded with a proportional detector. The sample height and 0-tilt were aligned by applying z-, ω-, and fine z-scans using the direct beam. The beam intensity during alignment was reduced by a Cu / Ni manual beam attenuator, and the mirror slit was also reduced to obtain a beam size of 0.09 mm. A parallel plate collimator receiving slit was inserted to select a single channel of the secondary beam collimator for alignment.

[0035] W(C x N 1-x ) y Layer grain width and orientation Electron backscatter diffraction (EBSD) analysis was used to determine the W(C x N 1-x ) y The grain width and orientation or texture of the layers were analyzed.

[0036] Preparation of polished cross sections was performed by embedding each of the CNMG120408-PM inserts in black conductive phenolic resin from AKASEL, which was subsequently ground to approximately 1 mm, and then polished in two steps using a diamond slurry solution: coarse (9 μm) and fine (1 μm). A final polish using colloidal silica solution was applied. All samples were mounted on a pretilt holder at a 70° angle to ensure maximum data collection efficiency. During data analysis, the coordinate system was aligned to correct for positional deviations within the microscope.

[0037] In all EBSD measurements, the collected data were all W(C x N 1-x ) y Grains from the WC-Co substrate were excluded from the data to ensure that they originated from the coating. Areas at least 100 μm wide and the full layer thickness in height were analyzed with a step size of 50 nm and speed 1 binning mode (622 × 512 pix) was used for all EBSD investigations. For grain width measurements, at least 700 grains were used for each grain width determination.

[0038] W(C x N 1-x ) y The orientation of the layers is determined by the W(C x N 1-x ) y The amount of W in the direction parallel to the surface normal was determined as the amount of W in the direction parallel to the surface normal. x N 1-x ) y The direction was selected. W(C x N 1-x ) y The layer orientation is <11-20>W(C x N 1-x ) y The amount of analysis area that was displaced within 30° from the direction of the sigma was calculated as the amount of analysis area that was displaced within 30° from the direction of the sigma. One automated cleanup step was used to gently reduce the noise level of the data. W(C x N 1-x ) y The orientation of the layer is x N 1-x ) y The analysis area is defined from the EBSD results for the cross section of the layer, with a width of 100 μm and a height of W(C x N 1-x ) y is the layer thickness, and W(C x N 1-x ) y The surface normal of the layer is parallel to the growth direction of the layer, and more than 75% of the analyzed area is W(C x N 1-x ) yThe layer has a <11-20> direction within 30 degrees of the surface normal, and preferably more than 80% of the analysis area is W(C x N 1-x ) y The layer has a <11-20> orientation within 30 degrees of the surface normal.

[0039] By using EBSD with the same measurement area mentioned in the previous section, W(C x N 1-x ) y The average grain width of was analyzed. Grain width measurements were performed using the Aztec Crystal v.2.0 software package using grain size determination by fitted ellipse minor axis. An ellipse is fitted to each grain and the minor axis of each ellipse is determined as the grain width. One automated cleanup step was used to gently reduce the noise level of the data, discarding all grains with an area less than 5 pixels to ensure that no measurement noise was included, thus increasing the accuracy of the measurement. The grain threshold was set at 10°.

[0040] The reference pattern of WC, Acta Crystallogr, [ACCRA9], 1961, Vol. 14, pp. 200-201 was used for the EBSD measurement of W(C x N 1-x ) y A total of 53 reflectors were used for the measurements.

[0041] A Zeiss Supra 55VP equipped with an Oxford Symmetry EBSD detector was used for all EBSD measurements. The accelerating voltage was set at 20 kV and a probe current of 10–30 nA was used.

[0042] SEM survey: SEM investigations were performed on a Zeiss Supra 55VP microscope with an accelerating voltage of 3 kV and a probe current of 300 pA.

[0043] Orientation of TiCN and α-Al2O3 layers To investigate the orientation of the TiCN and alumina layers, X-ray diffraction was performed on the flank face of the cutting tool insert using a PANalytical CubiX3 diffractometer equipped with a PIXcel detector. The coated cutting tool insert was mounted in a specimen holder, ensuring that the flank face of the cutting tool insert was parallel to the reference surface of the specimen holder and also that the flank face was at the appropriate height. Cu Kα radiation was used for the measurements, with a voltage of 45 kV and a current of 40 mA. 1 / 2 degree anti-scatter slits and 1 / 4 degree divergence slits were used. The diffraction intensity from the coated cutting tool was measured over the range of 20°-140° 2θ, i.e., an incidence angle θ range of 10-70°.

[0044] Data analysis, including background removal of the data, Cu Kα2 stripping and profile fitting, was performed using PANalytical's X'Pert HighScore Plus software. A brief overview of the fitting is given below. The output from this program (integrated peak areas of the profile fitting curve) was then used to calculate the texture coefficients of the layers by comparing the ratio of the measured intensity data to the standard intensity data from the PDF-card for a particular layer (e.g., TiCN or α-Al2O3 layers) using Harris' equation (1) disclosed above. Since the layers have a finite thickness, the relative intensities of pairs of peaks at different 2θ angles will differ from those for the bulk sample due to differences in path lengths through the layers. Therefore, in calculating the TC value, a thin film correction was applied to the extracted integrated peak area intensities of the profile fitting curve, taking into account the linear absorption coefficients of the layers as well. Possible further layers, for example above the α-Al2O3 layer, will affect the X-ray intensity entering the α-Al2O3 layer and exiting the entire coating, and so corrections must be made for these as well, taking into account the linear absorption coefficients of the respective compounds in the layer. A similar procedure applies to the XRD measurement of a TiCN layer, if the TiCN layer is located, for example, below an α-Al2O3 layer. Alternatively, further layers such as TiN above the alumina layer can be removed by methods that do not substantially affect the XRD measurement results, for example by chemical etching.

[0045] The texture coefficients TC(hkl) for different growth directions of columnar grains in TiCN layers were calculated according to the Harris formula. TIFF2024519616000003.tif19170where I(hkl) is the measured (integrated area) intensity of the (hkl) reflection, I0(hkl) is the standard intensity according to ICDD PDF-Card No. 42-1489, and n is the number of reflections used in the calculation. In this case, the (hkl) reflections used are (1 1 1), (2 0 0), (2 2 0), (3 1 1), (3 3 1), (4 2 0), (4 2 2) and (5 1 1).

[0046] To investigate the texture of the α-Al2O3 layer, X-ray diffraction was performed using Cu Kα radiation and the texture coefficients TC(hkl) for different growth directions of the columnar grains of the α-Al2O3 layer were calculated according to the Harris formula, where I(hkl) = measured (integrated area) intensity of the (hkl) reflection, I0(hkl) = standard intensity according to ICDD PDF-Card No. 00-010-0173, n = number of reflections used in the calculation. In this case, the (hkl) reflections used are (1 0 4), (1 1 0), (1 1 3), (0 2 4), (1 1 6), (2 1 4), (3 0 0) and (0 0 12). The measured integrated peak areas are thin film corrected and corrected for any further layers above (i.e. on) the α-Al2O3 layer before calculating said texture coefficients.

[0047] It should be noted that overlapping peaks is a phenomenon that can occur, for example, in the X-ray diffraction analysis of coatings containing several crystalline layers and / or coatings deposited on substrates containing crystalline phases, and that needs to be taken into account and compensated for. The overlapping of peaks from the α-Al2O3 layer with peaks from the TiCN layer can affect the measurement and therefore needs to be taken into account. Also, for example, the overlapping of peaks from WC in the substrate and W(C) in the coating can be a problem. x N 1-x ) y It should be noted that also have diffraction peaks that can affect the measurement and therefore need to be taken into consideration.

[0048] Embodiments of the present invention will now be described with reference to the accompanying drawings. [Brief description of the drawings]

[0049] [Figure 1] FIG. 1 is a cross-sectional SEM micrograph of the W(CxN1-x)y layer of a coated cutting tool (sample E1) according to an embodiment of the present invention, showing the W(CxN1-x)y layer (1), the substrate (2), the TiCN layer (3) and the α-Al2O3 layer. [Diagram 2] FIG. 2 is an EBSD band contrast micrograph of the coated cutting tool shown in FIG. 1 showing the W(CxN1-x)y layer (1), the substrate (2), the TiCN layer (3) and the α-Al2O3 layer. [Diagram 3] FIG. 2 is an enlarged view of the W(CxN1-x)y layer of the coated cutting tool shown in FIG. [Figure 4] FIG. 1 is a cross-sectional SEM micrograph showing a too thin W(CxN1-x)y layer of a coated cutting tool according to the reference (sample C). [Diagram 5] Grazing incidence X-ray diffractogram of sample E1. The dashed lines indicate the peak positions in the δ-WC criterion (Z. Anorg. Allg. Chem., 1926, Vol. 156, pp. 27-36), the numbers indicate the crystal planes to which the peaks belong. The intensity scale is logarithmic to highlight the lower intensity peaks. The diffractogram shows that only the hexagonal δ-WC phase is present in the coating. EXAMPLES

[0050] The embodiments of the present invention will be disclosed in more detail with reference to the following examples, which should be construed as illustrative and not limiting of the embodiments. In the following examples, coated cutting tools (inserts) were manufactured, analyzed and evaluated in cutting tests.

[0051] Base material Cemented carbide substrates with an alternative binder, referred to herein as NiFeCo binder, were produced using a binder comprising about 80.7 wt% Ni, 13.7 wt% Fe, and 5.6 wt% Co. The binder content in the cemented carbide was about 7 wt%. Cemented carbide substrates with an alternative binder were produced from a powder mixture having a composition of about 6.09 wt% Ni, 1.02 wt% Fe, 0.039 wt% Co, 1.80 wt% Ti, 2.69 wt% Ta, 0.41 wt% Nb, 0.09 wt% N, and the balance WC. The powder mixture was milled, dried, pressed, and sintered at 1450°C. The sintered cemented carbide substrates had a binder-rich surface zone from the substrate surface to a depth of about 30 μm into the body that was essentially free of cubic carbides as measured by optical microscopy. The amount of carbon in the powder was about 6.07 wt%, while the amount of carbon measured in the chemical analysis of the sintered cemented carbide was about 5.87 wt%. The sintered cemented carbide contained about 0.4 wt% Co, 1.0 wt% Fe, and 5.9 wt% Ni. The Co mainly came from the milling bodies that were worn during the milling step. No free graphite or eta phase was observed in SEM micrographs of the cross-section of the cemented carbide substrate.

[0052] As a reference, cemented carbide substrates with Co in metal binder, referred to herein as Co binder, were produced from a powder mixture with a composition of about 7.20 wt% Co, 1.80 wt% Ti, 2.69 wt% Ta, 0.41 wt% Nb, 0.09 wt% N and the balance WC. The powder mixture was milled, dried, pressed and sintered at 1450°C. The sintered cemented carbide substrates had a Co-rich surface zone from the substrate surface to a depth of about 23 μm into the body that was essentially free of cubic carbides as measured by optical microscopy. The sintered cemented carbide substrates contained about 7.2 wt% Co. No free graphite or eta phase was observed in SEM micrographs of cross sections of the cemented carbide substrates. These substrates are included herein as references and did not have any problems related to Ni diffusion.

[0053] The geometry of the cemented carbide substrate was that of ISO type CNMG120408 for turning.

[0054] Coating Deposition CVD coatings were deposited on the two cemented carbide compositions. Prior to the deposition of the coatings, all substrates were cleaned with a mild blasting step to remove the outermost metal from the surface. Shortly before deposition, the substrates were cleaned in an ethanol bath for 30 minutes.

[0055] In a hot-wall horizontal tubular furnace reactor, which is described in detail in J. Gerdin Hulkko, Muspel and Surtr: CVD system and control program for WF6chemistry, Licentiate thesis, Monograph, Uppsala University, 2019, W(C x N 1-x ) y The layers were deposited. Here, the main characteristics of the reactor system are described. The tubes are made of ferritic iron-chromium-aluminium alloy from Kanthal. The inner tube, made of isotropic graphite, prevents extensive etching of the outer tube and has an internal diameter of 47 mm. The tube has a cold zone 175 mm long before reaching the furnace. The furnace has a 130 mm unheated zone followed by three separate heated zones of 250 mm, 500 mm, 250 mm, and finally a 130 mm unheated zone. The temperature in the heated zones is controlled by a Eurotherm 3216 PID controller and a K-type thermocouple is installed in the middle of each zone on the outside of the reactor tube and inside the furnace. The inner temperature of the central zone was calibrated using a K-type thermocouple inserted through a 3 mm O-ring sealed port. During the process, the three heated zones were maintained at the same temperature.

[0056] The precursor flows are controlled by MKS GM50A mass flow controllers for WF6 (5.5 purity), H2 (5.6 purity) and Ar (6.0 purity) and by MKS 1152C mass flow controllers maintained at a temperature of 40°C for CH3CN (>99.9% purity). The CH3CN evaporator cylinder is maintained at 25°C and the pipes between the cylinder and the mass flow controllers are maintained at 45°C. All other gases are maintained at room temperature in the cylinders. Gases are transported in 316 stainless steel pipes, with silver-plated VCR or copper gaskets used at the connections. The bulk gas (H2 diluted with Ar) enters the reactor tube directly at the front of the reactor. The other two precursors (WF6 with Ar and CH3CN with Ar) are transported in separate Inconel 600 pipes through the first heated zone and enter the reactor tube 25 mm inside the central heated zone. S20N Roots pump from Ebara technologies (max capacity 100m 3 / hour, final pressure 3.75 x 10 -2 Low pressure is maintained by a 1 Torr pressure chamber. Gas flow is throttled by an O-ring sealed butterfly valve (MKS153D) and regulated by a PID vacuum control system (MKS946). A 1 Torr full range temperature stabilized capacitance manometer (MKS627B) is used for pressure measurements. Pressure readings were calibrated by pumping the system to the high vacuum range with a turbomolecular pump.

[0057] The deposition zone was between 90 and 230 mm from the gas mixing point, and coatings of uniform thickness, the same crystalline phase and the same dominant texture could be obtained.

[0058] W(C x N 1-x ) y was deposited using 1.8 vol.% WF, 1.2 vol.% CHCN, 25 vol.% H and the balance Ar at 715 °C and a pressure of 133 Pa. The total gas flow was set at 350 sccm and the deposition rate was approximately 0.5 μm per hour.

[0059] Samples C, D, E1, E2, F and G were then transferred for deposition of additional layers on a radial Ionbond Bernex™ type CVD machine, size 530, capable of accommodating 10,000 half-inch size cutting inserts.

[0060] First, the substrate was coated with a TiN layer using TiCl4, N2 and H2 at 885° C. The TiN deposition time was adapted to achieve a total TiN layer thickness of 0.4 μm.

[0061] Then, a TiCN layer of about 8 μm was deposited using well-known MTCVD techniques using TiCl4, CH3CN, N2, HCl and H2 at 885 °C. The volume ratio of TiCl4 / CH3CN in the initial part of the MTCVD deposition of the TiCN layer was 6.6, while a TiCl4 / CH3CN ratio of 3.7 was used in the subsequent period. Details of the TiN and TiCN deposition are shown in Table 1. TIFF2024519616000004.tif37170

[0062] After deposition of the TiCN outer layer, the temperature was increased from 885° C. to 1000° C. in an atmosphere of 75 vol. % H2 and 25 vol. % N2.

[0063] A 0.7-2 μm thick tie layer was deposited at 1000 °C on top of the MTCVD TiCN layer by a process consisting of four separate reaction steps. The first HTCVD TiCN step used 400 mbar TiCl4, CH4, N2, HCl and H2, then the second step (TiCNO-1) used 70 mbar TiCl4, CH3CN, CO, N2 and H2, then the third step (TiCNO-2) used 70 mbar TiCl4, CH3CN, CO, N2 and H2, and finally the fourth step (TiN-3) used 70 mbar TiCl4, N2 and H2. During the third deposition step, the CO gas flow rate was increased linearly in succession from the start value to the stop value as shown in Table 2. All other gas flow rates were kept constant, so the overall gas flow rate increases. The concentrations of all gases are somewhat affected by this. The bond layer was oxidized in a mixture of CO2, CO, N2 and H2 for 4 min before the initiation of subsequent Al2O3 nucleation.

[0064] The details of the tie layer deposition are given in Table 2. TIFF2024519616000005.tif63170

[0065] On top of the tie layer, an α-Al2O3 layer was deposited. All α-Al2O3 layers were deposited in two steps at 1000° C. and 55 mbar. The first step used 1.2 vol.% AlCl3, 4.7 vol.% CO2, 1.8 vol.% HCl and remaining H2 to produce α-Al2O3 of about 0.1 μm, and the second step disclosed below produced a total α-Al2O3 layer thickness of about 5 μm. The second step of the α-Al2O3 layer was deposited using 1.16% AlCl3, 4.65% CO2, 2.91% HCl, 0.58% H2S and remaining H2.

[0066] Samples F and G were also provided with an outermost wear indicator layer of TiN.

[0067] An overview of the samples is shown in Table 3. TIFF2024519616000006.tif110170

[0068] Coating Analysis ERDA was used to measure W(C x N 1-x ) y The composition of the layer was determined to be 43.7 at% W, 39.2 at% C, and 17.1 at% N, which has the chemical formula W(C 0.7 N 0.3 ) 1.3 Corresponds to.

[0069] Grazing incidence X-ray diffraction was used to determine the W(C x N 1-x ) y The phase of the layer was analyzed. The diffraction pattern showed that only the hexagonal phase was present in the coating, not the cubic WC. 1-x or WN y (0.5≦y≦2) reflections were not identified, nor were reflections of the tungsten-rich W2C phase (hexagonal close-packed W sublattice and C atoms in half of the octahedral voids). Reference reflections are calculated from Z. Anorg. Allg. Chem., 1926, Vol. 156, pp. 27-36.

[0070] W(C x N 1-x ) y When the layer was examined by SEM, it was found that W(C x N 1-x ) y The grains were found to be columnar. x N 1-x ) y The contact surface between the layers or W(C x N 1-x ) y No eta phase was found in the layers. Eta phase was found on the contact surface to the substrate of reference samples B1 and B2, as well as in the TiN and TiCN layers.

[0071] Average grain width and W(C x N 1-x ) y The layer orientation was analyzed by EBSD and the results are shown in Table 4. TIFF2024519616000007.tif42170

[0072] Due to the symmetry of the hexagonal δ-WC phase, the results can be interpreted as follows: within an angular range of ±30°, <0001> All possible crystallographic directions perpendicular to the direction are included. The selected spacing also includes the <0001> This means that the orientation deviates from the substrate surface plane by a maximum angle of 30°. The texture of the coating is therefore <0001> They can be described as hexagonal prisms that are oriented preferentially parallel to the substrate surface or slightly tilted therefrom.

[0073] The texture coefficients TC(hkl) of the TiCN and α-Al2O3 layers were analyzed by X-ray diffraction using Cu Kα radiation and θ-2θ scanning as disclosed above. TC(0 0 12) and TC(4 2 2) are shown in Table 5. TIFF2024519616000008.tif58170

[0074] From the X-ray diffraction analysis and the texture coefficient, W(C x N 1-x ) y The reference sample C with the layer has a W(C x N 1-x ) y It can be concluded that it shows a lower TC(4 2 2) and a lower TC(0 0 12) compared to the inventive sample D provided with a layer.

[0075] Cutting test Coated cutting tools of ISO type CNMG120408 were tested in longitudinal turning in bearing steel (100CrMo7-3) using the following cutting data: cutting speed v c :220m / min Cutting feed rate, f: 0.3mm / revolution Cutting depth, a p :2mm

[0076] A water-miscible metalworking fluid was used.

[0077] One cutting edge per cutting tool was evaluated.

[0078] In the analysis of crater wear, the area of ​​exposed substrate was measured using an optical microscope. 2 The tool was considered to have reached its end of life if it exceeded the size of the crater area of ​​0.2 mm. The wear of each cutting tool was evaluated by optical microscopy after 2 min of cutting. The cutting process and measurements after each 2 min of operation were then continued until the tool life scale was reached. 2 If exceeded, the time until the tool life criterion was fulfilled was estimated based on an assumed constant wear rate between the last two measurements. Besides the crater wear, the flank wear was also monitored. Three parallel tests were performed for each type of coating. The results, presented as the average tool life, are shown in Table 6. TIFF2024519616000009.tif34170

[0079] W(C x N 1-x ) y It can be concluded that the layered E2 sample outperforms the reference B2. As expected, reference A, which does not contain the interfering Ni in the metal binder phase of the cemented carbide, also performs well.

[0080] While the invention has been described in connection with various exemplary embodiments, it is to be understood that the invention is not limited to the disclosed exemplary embodiments, but on the contrary, is intended to cover various modifications and equivalent arrangements within the scope of the appended claims.

Claims

1. A coated cutting tool comprising a substrate at least partially coated with a coating, said substrate being made of a cemented carbide comprised of a hard constituent in a metal bond, said metal bond comprising more than 60 wt.% Ni, said coating comprising two or more layers, a layer adjacent to the substrate being W(C x N 1-x ) y layer, wherein 0.6≦x≦0.8 and 1.1≦y≦1.8, preferably 0.67≦x≦0.72 and 1.17≦y≦1.76; W(C x N 1-x ) y A coated cutting tool, the layer thickness being between 0.4 and 7 μm.

2. W (C x N 1-x ) y The coated cutting tool of claim 1 , wherein the layer is in the hexagonal phase.

3. W (C x N 1-x ) y 3. A coated cutting tool according to claim 1 or 2, wherein the layer is composed of columnar grains.

4. W (C x N 1-x ) y Coated cutting tool according to claim 1 or 2, wherein the average grain width of the layer is between 0.14 and 0.40 μm, preferably between 0.15 and 0.30 μm.

5. W (C x N 1-x ) y The layer is x N 1-x ) y The orientation measured by EBSD for a cross section of the layer is shown, with the analysis area being 100 μm wide and 100 μm high, with the total W(C x N 1-x ) y is the layer thickness, and W(C x N 1-x ) y The surface normal of the layer is parallel to the growth direction of the layer, and more than 75% of the analysis area is W(C x N 1-x ) y The layer has a <11-20> direction within 30 degrees of the surface normal, and preferably 80% or more of the analysis area is W(C x N 1-x ) y 3. The coated cutting tool of claim 1 or 2 having a <11-20> orientation within 30 degrees of the layer's surface normal.

6. A coated cutting tool according to claim 1 or 2, wherein the metal bond comprises 65-90 wt% Ni, preferably 70-87 wt% Ni, more preferably 75-85 wt% Ni.

7. A coated cutting tool according to claim 1 or 2, wherein the metal binder content in the cemented carbide is 3-20% by weight, preferably 5-15% by weight, most preferably 5-10% by weight.

8. A coated cutting tool according to claim 1 or 2, wherein the coating comprises a TiCN layer, preferably the thickness of the TiCN layer is between 6 and 12 μm.

9. The TiCN layer is measured by X-ray diffraction using Cu Kα radiation and θ-2θ scanning, according to the Harris equation: where I(hkl) is the measured intensity (integrated area) of the (hkl) reflection, and I 0 9. Coated cutting tool according to claim 8, wherein (hkl) are the standard intensities according to ICDD PDF-Card No. 42-1489, n is the number of reflections and the reflections used in the calculation are (1 1 1), (2 0 0), (2 2 0), (3 1 1), (3 3 1), (4 2 0), (4 2 2) and (5 1 1), and TC(4 2 2) is ≧3.5, preferably ≧4.

10. A coated cutting tool according to claim 1 or 2, wherein the total thickness of the coating is between 2 and 25 μm.

11. The coating preferably comprises a coating layer on the outermost surface of the cutting tool and a coating layer on the outermost surface of the cutting tool. x N 1-x ) y Al located between the layers 2 O 3 The coated cutting tool of claim 1 or 2, further comprising a layer of:

12. A 2 O 3 The layer is α-Al 2 O 3 The coated cutting tool of claim 11 which is a layer.

13. The α-Al 2 O 3 The layer exhibits a texture coefficient TC(hkl) defined according to the Harris equation, measured by X-ray diffraction using Cu Kα radiation and θ-2θ scanning, where I(hkl) is the measured intensity (integrated area) of the (hkl) reflection, and I 0 Coated cutting tool according to claim 12, characterized in that (hkl) are the standard intensities according to ICDD PDF-Card No. 00-010-0173, n is the number of reflections used in the calculation, the (hkl) reflections used are (1 0 4), (1 1 0), (1 1 3), (0 2 4), (1 1 6), (2 1 4), (3 0 0) and (0 0 12), and TC(0 0 12) is ≧5, preferably ≧6, more preferably ≧7.

14. A 2 O 3 A coated cutting tool according to claim 11, wherein the layer has a thickness of 4 to 8 μm.

15. 3. The coated cutting tool of claim 1 or 2, wherein the coating is a CVD coating.